Investigation and analysis of time response in Geiger mode avalanche photodiode - Dehghan, M.; Ahmadi, V.; Darabi, E. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
Statistical properties of the impulse response of avalanche photodiode (APDs) are determined. The model is based on recurrence equations. These equations are solved numerically to calculate the mean current impulse response and standard deviation as a function of time. In this paper, we investigate the effects of parameters such as ionization coefficient-multiplication thickness product (αw), dead space, excess noise factor, mole fraction, temperature on the mean current impulse response of APD in the Geiger mode.
Optica Applicata, Vol. 40, 2010, nr 2, s. 471-479
Keywords: optyka; avalanche photodiode; Geiger mode; time response